Modification of blend reverse osmosis membranes using ZrO2 for desalination process purposes - Saleh O. Alaswad; Eman S. Mansor; Heba Abdallah; Ahmed M. Shaban (Applied Water Science)
Abstract Desalination of water is a crucial step in the process of obtaining potable water. One of the main challenges for the researchers is its efficient application and affordable preparation. It was planned to prepare the flat sheet membranes using cellulose acetate as a base polymer, and polyvinyl alcohol (PVA) as an additive with dosing of (0.1, 0.3, 0.5, and 0.7 wt%) from zirconium oxide (ZrO2) nanoparticle. SEM, TEM, and XRD analyses were used to characterize the generated ZrO2 nanoparticle in order to confirm its nano-size and crystal structure. The surface morphologies and existence of the dense layer, which is the typical property of the RO membrane capable of salt separation, were identified on the manufactured RO membranes by SEM. Membranes prepared by embedding 0.5 wt%ZrO2 with PVA/CA proved efficient as RO membranes using 2000 ppm NaCl and exhibited high salt rejection of 97% and water permeability of 12.5 LMH. Also, there is a decrease in the NaCl removal tendency was observed with the excessive dosages of ZrO2 with 0.7 wt%, which was due to the concentration polarization, which blocks the pores on the surfaces of the membranes. The antifouling behavior of the prepared membranes was tested using bovine serum albumin (BSA), the results indicate the low irreversible resistance, total fouling resistance, and high flux recovery ratio compared to the neat membrane. The prepared membranes have a stable salt rejection and water productivity even after demonstrating with chlorine (25–100 mg l−1 of NaOCl for 120 min).